The Calmé Mind - Mohd Suhaili, Amira Liyana; Sollehan, Nur Alya Damia; Mohamad Nazri, Nur Amani Akma; Zali, Nur Asikin (2025)
The Calmé Mind is a modern café concept that blends mental health awareness with relaxation by offering a supportive environment where visitors can receive AI-assisted emotional assessments upstairs and enjoy mood-enhancing food and beverages downstairs while they wait. Through facial recognition and body scanning, the system provides personalized recommendations, while the café’s calming atmosphere, healthy menu, and digital queue system create a seamless and comforting experience. Targeting students, professionals, and urban communities, the Mental Hub Café aims to make mental wellness more accessible by combining smart technology with a warm, inclusive space.